Piwulang Estri sebagai Bentuk Reportase tentang Wanita Jawa - Arsanti Wulandari (Manuskripta, 2016)
A reportage is an act of reporting. A reportage can be based either on investigation or a written source. The old document in the form of a manuscript can be regarded either as a work or as a document, which repporting an evidence in the past. This circumstance can be said to the manuscript containing Piwulang Estri. Written in 1856 CE, during the time when Javanese woman, as reflected in the text, getting a high position in the mind of author. Women are depicted in symbolic ways in three texts in Piwulang Estri, i.e. Batik Suluk, Suluk Tenun, and Suluk Tanen. Tanen is derivatife form from the word tani, here the author made allusion of preparing 'land'. Women interpreted as a ‘land’, means to prepare the next generation. Weaving symbolise the process of educating the next generation, and batik as the process of “coloring” or giving form the next generation. The concepts or philosophy regarding a women from the psychology point of view are depicted in three Suluk texts in the Piwulang Estri. --- Sebuah reportase adalah sebuah pelaporan. Adanya reportase bermakna adanya informasi yang disampaikan dari satu pihak ke pihak lain. Sebuah reportase dapat didasarkan pada sebuah pengamatan ataupun sumber tertulis. Naskah dapat dikatakan sebagai sebuah karya yang dapat dimaknai juga sebagai sebuah dokumen, yang merekam kejadian pada masa lampau. Demikan pula naskah dengan judul Piwulang Estri. Naskah ini adalah naskah yang ditulis tahun 1856. Pada masa itu tampaknya wanita mendapatkan posisi yang bukan sembarangan. Wanita digambarkan dalam berbagai simbol yang termuat dalam tiga teks suluk di dalamnya, yaitu Suluk Batik, Suluk Tenun, dan Suluk Tanen. Tanen dari kata tani yang menggambarkan proses menyiapkan lahan. Wanita dimaknai sebagai lahan untuk menyiapkan generasi penerus, tenun untuk proses mendidik generasi penerus, dan batik sebagai proses mewarnai atau membentuk generasi penerus. Konsep-konsep ataupun filosofi dalam memandang wanita dari sisi psikologi banyak digambarkan dalam ketiga teks suluk yang terbungkus dalam teks Piwulang Estri ini.